Revisión del uso de sellos químicos para el control de agua de producción en pozos petroleros (2018)
Production water is known in the oil industry as the fluid that accompanies oil and gas. It contains high concentrations of salts, metals and organic compounds, generating management problems due to its volume and toxicity. In Colombia, it is estimated that about 11.6 barrels of water are produced for each barrel of crude obtained. This excessive water production overloads the surface treatment systems, affecting productivity. Due to these problems that occur with greater intensity, polymer treatments that increase the rate of hydrocarbon production are being carried out. Here is a brief review of the theory and practice around this topic.